Accountants’ IT Competencies and IT Responsibilities in Supporting IT Sustainability Practice: The Variations of Students’ Perspective - Hendri Kwistianus; Saarce Elsye Hatane; Melissa Wong; Eden Victoria; Angela Irena Gunawan (Master of Management, School of Business and Management, Petra Christian University, 2021)
This study looks at the variability of accounting students’ perceptions in Indonesia on the importance of IT competence and IT responsibility for accountants and the importance of IT sustainability practices. This study measures different perceptions of accounting students based on gender (male and female), year of study (junior and senior), and the type of university (public and private). The majority of accounting students agree with the importance of accountants’ role in IT sustainability practices by utilizing information systems. However, differences in perceptions of accountants’ IT responsibility, accountants’ IT competence, and the importance of IT sustainability practice are found in the senior and junior student groups. This finding results in junior students being higher than senior students in understanding the importance of the accountants’ role in the IT sustainability practice. Differences were also found in the groups of students from public and private universities, where students in public universities have a higher perception than students in private universities toward IT sustainability issues. There is no difference in perception in the gender group. This study can be helpful for higher education providers and teachers in accounting who play an essential role in supporting students to understand the practical implementation in accounting professions regarding their role in sustainability through the utilization of information technology.